2023
DOI: 10.3390/medicina59071204
|View full text |Cite
|
Sign up to set email alerts
|

Release of Monomers from Dental Composite Materials into Saliva and the Possibility of Reducing the Toxic Risk for the Patient

Abstract: Background and Objectives: The objective of this study was (1) to measure the amount of monomers released into the saliva depending on the time elapsed after the hardening of the composite and on the type of monomer used; and (2) with the prolongation of the light-curing procedure, to publish information on whether it would be possible to influence the level of leached monomers. Materials and Methods: HPLC technique was used to monitor the levels of the unpolymerized monomers Bis-GMA, Bis/EMA, TEGDMA, and UDMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The molecular weights of these monomers vary; TEGDMA has the most negligible molecular weight at 286.32 g/mol, UDMA is next at 470.56 g/mol, and Bis-GMA is the heaviest at 512.60 g/mol. Interestingly, there is a relationship between these monomers’ molecular weight and toxicity; studies have shown that toxicity tends to rise with molecular weight in the following order: TEGDMA < UDMA < Bis-GMA [ 40 ]. This implies that AEF’s increased production of these heavier, more toxic monomers may cause its increased toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular weights of these monomers vary; TEGDMA has the most negligible molecular weight at 286.32 g/mol, UDMA is next at 470.56 g/mol, and Bis-GMA is the heaviest at 512.60 g/mol. Interestingly, there is a relationship between these monomers’ molecular weight and toxicity; studies have shown that toxicity tends to rise with molecular weight in the following order: TEGDMA < UDMA < Bis-GMA [ 40 ]. This implies that AEF’s increased production of these heavier, more toxic monomers may cause its increased toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical procedures could be applied to minimize the release of unpolymerized monomers [ 17 , 18 , 19 , 20 , 21 , 40 , 41 , 42 ]: rubber dam use for restoration making, using a curing lamp with sufficient power (>1000 mW/cm 2 ), bringing the fiber of the curing lamp closer to the material to be cured, and prolonging curing time or, in the case of restoration making, adding a second curing step after covering the restoration with a glycerin film. Unpolymerized monomers are present on the surface of the material because of the inhibition of polymerization induced by oxygen [ 40 , 41 ]. It was also demonstrated that brushing the restoration surface with pumice or water/air spray eliminated most residual monomers [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unpolymerized monomers are present on the surface of the material because of the inhibition of polymerization induced by oxygen [ 40 , 41 ]. It was also demonstrated that brushing the restoration surface with pumice or water/air spray eliminated most residual monomers [ 41 , 42 ]. A gargle with warm water 30 s after orthodontic bonding [ 20 ] or restoration bonding [ 41 ] could also reduce the level of residual monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some clinical procedures could be applied to minimize the release of unpolymerized monomers [15][16][17][18][19]36,37]: rubber dam use for restorations making, using a curing lamp with sufficient power (>1000 mW/cm 2 ), bring the fiber of the curing lamp closer to the material to be cured and prolonged curing time or in case of restoration making a second curing step after covering the restoration with a glycerin film. Unpolymerized monomers are present on the surface of the material because the inhibition of polymerization induced by oxygen [36,37]. It was also demonstrated that brushing the restoration surface with pumice or water/air spray eliminated most residual monomers [36,37].…”
Section: Clinical Recommendationsmentioning
confidence: 99%